Pengaruh Bauran Pemasaran Terhadap Keputusan Pembelian Produk Mebel Siantano Pada Misi Depo Bangunan Di Kota Makassar - Rombe, Elimawaty; Kristina Parinsi, Welimas (CV. Lafadz Jaya, 2023)
In Makassar City, PT. Mega Indah Saru Timor (Building Depot Mission), Siantano Furniture Products are being purchased. This study intends to ascertain the impact of the marketing mix on those decisions. The Accidental Sampling approach was chosen in this study because the sample consisted of 96 Siantano furniture buyers that the researchers encountered by chance and thought would make good responses. Utilizing surveys, interviews, and documentation, data was gathered. Multiple linear regression analysis using SPSS version 20 is the data analysis method employed, along with the t test and F test for hypothesis testing. According to the value of Fcount 77.133 > Ftable 2.47, the findings of the F test indicated that the marketing mix's independent factors, namely the product, price, distribution, and promotion, combined had a positive and significant impact on purchase decisions. Additionally, the partial test results demonstrate that the three independent variables, Product, Place, and Promotion, have tcount values that are greater than ttable (1.986), with respective values of 5.926, 2.13, and 3.45. The Price variable, which has a tcount value of (1.599), is between (1,986) and (1,986). The product variable is the one of the four independent variables that has the biggest impact on consumer decisions.